An Experimental Study on Aerodynamic Interaction Between a Boundary Layer Generated by a Smooth And Rough Wall and a Wake Behind a Spire - Nurizzatul Athika, Rahmat; Hagishima, Aya; Ikegaya, Naoki; Tanimoto, Jun (Kyushu University, 2016)
A wind tunnel experiment to assess the flow characteristics of the wake behind a spire mounted normal to the wind tunnel floor was conducted to clarify the interaction between the wake flow and the wall shear boundary layer. To reproduce the contrasting boundary layer depth, two types of walls—a smooth wall and a regular cube array—were adopted; for each wall, the spanwise distribution of the streamwise velocity was measured at two downwind positions and seven heights within and above the wall boundary layer with and without a spire. The spanwise distribution of the wake generated by the spire far above the wall boundary layer with low turbulence agreed with the well-known function for two-dimensional (2D) wake flow, derived theoretically from the gradient-diffusion model, despite the weak asymmetry of the inflow. In contrast, the spanwise distribution of the wake within or near the outer edge of the wall boundary layer showed different trends from that of the 2D wake flow. In the former, the expansion of the wake width is compressed in the lateral direction by the turbulence of the wall boundary layer and the velocity deficit of the wake is sustained far from the spire.